The contested origins of the 1865 Arabic Bible : contributions to the nineteenth century Nahḍa - Grafton, David D. (The History of Christian-Muslim Relations, 2015)
This study examines the history of an Arabic Bible translation of American missionaries in late Ottoman Syria. Comparing the history of this project as recorded by the American missionaries with private correspondence and the manuscripts of the translation, The Contested Origins of the 1865 Arabic Bible provides new evidence for the Bible's compilation, including the seminal role of Syrian Christians and Muslims. This research also places the project within the wider social-political framework of a transforming Ottoman Empire, where the rise of a literate class in Beirut served as a catalyst for the Arabic literary renaissance (Nahḍa), and within the international field of New Testament textual studies.